2015
DOI: 10.1002/fsn3.202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium alginate coating enriched with horsemint (Mentha longifolia) essential oil on the quality of bighead carp fillets during storage at 4°C

Abstract: Effect of sodium alginate coating enriched with horsemint essential oil (HEO) on the quality of bighead carp (Aristichthys nobilis) fillets at refrigeration temperature (4 ± 1°C) was studied. Bighead carp fillets were coated with neat sodium alginate (SA) and sodium alginate containing 0.5 and 1% v/v of HEO and their quality changes in terms of total volatile basic nitrogen (TVB-N), peroxide value (PV), thiobarbituric acid (TBA), and microbial counts were investigated. SA coating enriched with the essential oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 38 publications
6
40
0
Order By: Relevance
“…In general, after 10 days of storage at 4 °C, SA, TP, and SA‐TP treatment inhibited TBARS increase, with SA‐TP providing the greatest level of inhibition. These results are similar to previous studies, in which lipid oxidation was delayed by SA (Heydari et al., ) or TP (Yi et al., ) treatment, due to their antioxidant properties.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In general, after 10 days of storage at 4 °C, SA, TP, and SA‐TP treatment inhibited TBARS increase, with SA‐TP providing the greatest level of inhibition. These results are similar to previous studies, in which lipid oxidation was delayed by SA (Heydari et al., ) or TP (Yi et al., ) treatment, due to their antioxidant properties.…”
Section: Resultssupporting
confidence: 93%
“…() and Heydari et al. () for refrigerated northern snakehead and bighead carp, respectively, coated with sodium alginate.…”
Section: Resultsmentioning
confidence: 99%
“…Acting as a barrier against oxygen transfer, other researchers believe that coating leads to inhibiting the growth of the aerobic bacteria (Song et al, ). These findings are consistent with Lu et al (), Song et al () and Heydari et al () for refrigerated northern snakehead, bream and big head carp, respectively, coated with sodium alginate. Alvarez, Ponce, and Moreira () reported anti‐psychrotrophic bacterial activity of RE in chitosan‐coated fresh cut broccoli during refrigerated storage.…”
Section: Resultssupporting
confidence: 92%
“…It exceeded the limit by day 7 for control and by day 10 for C-A coated samples. Such difference may be related to the antibacterial effect of cellulose and alginate coating as reported by other researchers (Hamzeh and Rezaei 2012;Ariaii et al 2014;Raeisi et al 2014;Heydari et al 2015). Ariaii et al (2014) and Abdollahi et al (2014) reported that exceeded limit for TVB-N of silver carp fillet was at day of 8 during the refrigerator storage.…”
Section: Total Volatile Basic Nitrogen (Tvb-n)mentioning
confidence: 79%
“…Alginate solution was prepared by dissolving 30 g of sodium alginate powder in 2 L distilled water to obtain a 1.5 % w/v alginate solution using a magnetic stirring plate at 70°C and 1200 rpm for 30 min, then cooled to room temperature (Heydari et al 2015).…”
Section: Coating Preparationmentioning
confidence: 99%